Provision of an out-of-hours emergency endoscopy service: the Leicester experience. Issue 4 (22nd May 2013) - Ramiah, Rekha; Wurm, Peter
Abstract : Introduction: The British Society of Gastroenterology (BSG) Strategy document 'Care of patients with Gastrointestinal (GI) disorders' recommends that all acute hospitals should have arrangements for out-of-hours (OOH) endoscopy staffed with appropriately trained endoscopists. The UK national audit published in 2010 found that only 52% of hospitals across the UK had a formal consultant-led OOH endoscopy on-call rota. The University Hospitals of Leicester (UHL) established a consultant-led rota in 2006, which now provides 24/7 endoscopy cover. To define the workload of a newly established OOH service, we examined procedures performed since the introduction of an OOH service in 2006. Methods: The audit period covered August–January (6 months) for each of five consecutive years. Data were gathered from formal endoscopy reports on Unisoft reporting tool and OOH record books. We examined indication for endoscopy, timing of procedure, findings at index endoscopy, intervention and immediate outcome. Results: Across the three UHL sites, data on 982 patients were analysed. Eighty-one percent of procedures performed were gastroscopies. 63% of the procedures were performed for GI bleed indications. Over the five years, there was an overall increase in the number of procedures performed where no pathology was found. Immediate outcomes postendoscopy were good, with over 90% being returned to their base ward. Conclusions: The experience at UHL appears to show a trend towards an increasing number of procedures performed OOH, with fewer positive findings and less need for therapy. A likely contributing factor is the ongoing shortage of medical beds, requiring more routine work to be done OOH in order to expedite discharges. However, early specialist endoscopic input is likely to improve patient management. The impact of an OOH service on other services, however, needs to be carefully considered.